Factor input substitution in Irish manufacturing - Stefanie A. Haller; Marie Hyland (The Economic and Social Research Institute (ESRI), 2014)
We use a translog cost function to model production in the Irish manufacturing sector over the period from 1991 to 2009. We estimate both own- and cross-price elasticities and Morishima elasticities of substitution between capital, labour, materials and energy. We find that capital and energy are substitutes in the production process. Across all firms we find that a 1% rise in the price of energy is associated with an increase of 0.1% in the demand for capital. The Morishima elasticities, which reflect the technological substitution potential, indicate that a 1% increase in the price of energy causes the capital/energy input ratio to increase by 1.58%. The demand for capital in larger, more energy-intensive, foreign-owned and export-oriented firms is less responsive to increases in energy prices. We also observe a sharp decline in firms' responsiveness between the first half of the sample period (the 1990s) and second half (the 2000s).
Keywords: 330; factor demand; substitution between energy and capital; firm-level panel data